INTERNATIONAL AND RUSSIAN LEGAL PRACTICE FOR THE DEVELOPMENT OF INCLUSIVE EDUCATION - Kupriyanova, Lyudmila; Rodionov, Alexander; Albov, Alexey; Ognev, Aleksandr (Revista Inclusiones, 2020)
The article addresses a relevant research topic accounting for the orientation of modern European countries, including the Russian Federation, on the development of a socially-oriented type of economy and solving the social problems of people with disabilities. As a result of the conducted analysis of the legal possibilities and realities of people with disabilities obtaining professional education, we can conclude that the state takes certain steps to solve the issue but many problems remain unresolved. To overcome these issues, it is primarily important to develop inclusive education across Russia, which requires the psychological readiness of teachers, technical staff, and parents of children with disabilities. It is necessary to ensure the accessibility of the buildings of educational institutions for the education of children with various forms of disability. Despite the existence of a large array of regulations forcing educational institutions to provide accessibility for people with disabilities, educational institutions are unable to promptly follow them without additional funding. In general, all states need to form a positive attitude towards people with disabilities in their citizens. This type of measure can help to increase the accessibility of education for people with disabilities.